Professional training in dentistry: Program contribution oral health care to the low-income population, Vitória-ES - Lovo Campostrini, Vitor; Baroni de Carvalho, Raquel; Batitucci dos Santos Daroz, Claudia; Dias Daroz, Luiz Gustavo; Sarcinelli, Aline; Batitucci, Roberta (Guará Journal, 2025)
Extramural activities enable students to gain insight into the structural dimensions of public health services, participate in providing care to the population, understand oral health policies, the role of the dentist, and the social context in which they will eventually enter. The objective of this work is to present the Extension Program "Oral Health Care for Low-Income Populations," highlighting its importance in the education of Dentistry students at the Federal University of Espírito Santo (UFES). This project has contributed to the education of this institution's students for 34 years, providing insight into the social context of a financially disadvantaged population and developing skills acquired at the university. It is concluded that projects like this are crucial for the development of professionals aware of the real needs of the population in the region where they will work, capable of meeting this demand with ethics and professionalism.
Keywords: Community-institutional relations; Teaching care integration services; Professional practice